Study of the exotic μ-e conversion in nuclei using RQRPA - Ren, Zhongzhu; Faessler, A.; Kosmas, T. S. (HNPS Advances in Nuclear Physics, 2020)
The neutrinoless muon-to-electron conversion in nuclei is studied by using the renormalized quasiparticle random-phase approximation (RQRPA). This generalization of RPA is more reliable for the extremely small (μ-,e-) transition matrix elements than the ordinary QRPA because it restores the Pauli principle to a large extent. We apply the method to a set of nuclei throughout the periodic table, but we specifically investigate the 48Ti and 208Pb nuclei which are currently used as stopping targets at the PSI μ-e conversion experiments with the SINDRUM II spectrometer.